The effective role of the school administration in increasing student achievement in public schools at Ajloun Governorate from the teachers’ point of view - Jadullah, Saddam Hanna Rezqullah (Journal of Educational and Psychological Sciences, 2020)
This study aimed to increase the students’ achievement at Ajloun Government school from teacher perspectives by activating the school administration the study sample consists of (267) male teacher and female teachers. To achieve the objectives of the study, a questionnaire was used as a tool for data collection; it consisted of (24) paragraphs. The result showed that The role of Effective school administration in increasing the students’ achievement was high with (3.92) score also the result showed there is significant differences refers to years of experiences in favor of (more than 10 years) and there is no significant differences refers to school educational stage. According to the results, the researcher proposed a set of recommendations, the most important of which was: the school administration should strive to develop and renew in its work.